Effect of Infant RSV Infection on Memory T Cell Responses at Age 2-3 Years - Chirkova, Tatiana; Rosas-Salazar, Christian; Gebretsadik, Tebeb; Jadhao, Samadhan J.; Chappell, James D.; Peebles, R. Stokes; Dupont, William D.; Newcomb, Dawn C.; Berdnikovs, Sergejs; Gergen, Peter J.; Hartert, Tina V.; Anderson, Larry J. (Frontiers in Immunology, 2022)
Background: It is unknown whether RSV infection in infancy alters subsequent RSV immune responses. Methods: In a nested cohort of healthy, term children, peripheral blood mononuclear cells (PBMCs) were collected at ages 2-3 years to examine RSV memory T cell responses among children previously RSV infected during infancy (first year of life) compared to those RSV-uninfected during infancy. The presence vs. absence of infant RSV infection was determined through a combination of RSV molecular and serologic testing. Memory responses were measured in RSV stimulated PBMCs. Results: Compared to children not infected with RSV during the first year of life, children infected with RSV during infancy had lower memory T cell responses at ages 2-3 years to in vitro stimulation with RSV for most tested type-1 and type-17 markers for a number of memory T cell subsets. Conclusions: RSV infection in infancy has long-term effects on memory T cell responses. This is the first study to show the potential for RSV infection in infancy to have long-term effects on the immune memory irrespective of the severity of the infection. Our results suggest a possible mechanism through which infant RSV infection may result in greater risk of subsequent childhood respiratory viral morbidity, findings also relevant to vaccine development.